(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
A 25 years old nulliparous regularly menstruating woman presented inShSMC Hospital with the complaints of swelling in the right side of vulva and Dysparunia for 4 months. The swelling was initially small and painless but later on it became painful. The swelling recurred after surgical treatment. Examination revealed a swelling in the right Labium majus which was about 4x3 cm, bulging into right side of vagina. It was diagnosed as a case of recurrent bartholin cyst but during surgical procedure it was apparent that the swelling was not bartholin cyst but some other fleshy structure. The removed mass was 7x4 cm. Histopathology revealed benign lesion containing hypocellular structure with large blood vessels and no malignancy. It was diagnosed as Aggressive angoimyxoma. Aggressive Angoimyxoma is a very rare mesenchymal tumor, uptil now only 200 case have been reported in the world. It is a slow growing benign tumor which is typically located in the pelvis and perineum. It often presents with asymptomatic perineal or vulval mass and may be confused with Bartholins cyst, lipoma or hernia. Local recurrence is upto 70%; metastasis is very rare. Treatment is surgical resection Histology reveals a mass of mixed mesenchymal origin with low mitotic activity.It is a hypocellular and highly vascular tumor with myxoid stroma. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 46-48